Studies on optical and photoluminescence properties of a-CNx thin films - Rahman, Z.A.; Ritikos, R.; Rahman, S.A. (2009)
Amorphous carbon nitride (a-CNx) thin films of different thicknesses were deposited by radio frequency plasma enhanced chemical vapour deposition technique by varying the deposition times. The refractive index, film thickness and optical energy gap were obtained from the optical transmission spectrum of the film in visible wavelength region. The photoluminescence emission intensity and wavelength due to ultraviolet excitation were studied and analysed. The effects of deposition time and film thickness on these properties were investigated. The deposition rate decreased with increasing deposition time to a stable saturation value. The optical energy gap decreased with increasing film thickness which is attributed to increase in presence of sp(2) bonding clusters in the film structure. Photoluminescence emission intensity and wavelength also showed dependence on film thickness.